The collective contribution of Chinese cities to territorial and electricity-related CO2 emissions. (10th July 2018) - Tong, Kangkang; Fang, Andrew; Li, Yang; Shi, Lei; Wang, Yangjun; Wang, Shuxiao; Ramaswami, Anu
Abstract: Many studies have quantified carbon emissions from a subset of cities in a nation, while few studies have estimated emissions from all cities in a nation to assess their collective contributions towards national total. This paper focuses on China and assesses the collective contribution of all cities to national carbon emissions, the share of carbon emissions by city types, and carbon emission per capita and per GDP. This paper describes the Chinese City Industrial-Infrastructure database including fuel/electricity use and heat supply in 644 cities, in which energy use is aligned with national data with ∼1% difference. It is found that direct carbon emissions from 644 Chinese cities collectively contribute to 62.4% of the national CO2 emissions. Further categorizing these cities based on population size, economic structure (Highly-Industrial, Highly-Commercial, and Mixed-Economy cities), and administrative level, it is found that Midsize cities (0.5–3 million) accounted for 38.1% of national CO2 emissions; Mixed-Economy cities contributed to about 40% of the national CO2 emissions; and city propers (all urban administrative districts in a city) collectively contribute to 42.9% of the national CO2 emissions. Direct emissions per capita ranged from 0.94 to 83.3 tonnes CO2 per person (8.85 tonnes/person on average). Direct emissions per GDP ranged from 0.01 to 2.60 kg CO2 per yuan -GDP (0.26 kg CO2 / yuan -GDP on average). Direct plus embedded emissions in electricity were also evaluated and found to have similar patterns as direct carbon emissions. These results enhance our understanding of the share of carbon emissions from Chinese cities and suggest the importance of focusing on certain city types for mitigation efforts.